自发性脑出血术后早期使用阿司匹林的可能性：来自中国学者的首个脑出血围手术期管理高级别循证依据 Possibility of Early Use of Aspirin after Spontaneous Intracerebral Hemorrhage Surgery: The First High-Level Evidence-Based Evidence for Perioperative Management of Intracerebral Hemorrhage from Chinese Scholars - 周航，陈高(ZHOU Hang, CHEN Gao) (Zhongguo cuzhong zazhi)
摘要： 自发性脑出血是全球范围内致死致残的重要疾病之一，尽管其外科手术治疗已日趋成熟，但相应的术后管理方案尚不明晰。其中，脑出血术后存活患者发生主要心脑及外周血管事件的风险显著增加，但现行指南尚未明确能否以及何时启动抗血小板治疗。近期发表的自发性脑出血患者神经外科手术后早期抗血小板治疗（early-start antiplatelet treatment after neurosurgery in patients with spontaneous intracerebral hemorrhage，E-start）研究表明，对于具有高缺血事件风险的脑出血患者，术后早期启动抗血小板治疗可带来显著获益，且不增加出血风险。作为国内首个脑出血围手术期管理的高级别循证证据，E-start研究有助于提高脑出血救治与管理水平，改善患者预后。 Abstract: Spontaneous intracerebral hemorrhage is one of the important diseases causing death and disability worldwide. Although surgical treatment has become increasingly mature, the corresponding postoperative management strategies remain poorly defined. In this context, patients who survive after intracerebral hemorrhage surgery have a significantly increased risk of major cardiovascular, cerebrovascular, and peripheral vascular events. However, current guidelines have not yet established clear recommendations on whether or when to initiate antiplatelet therapy. The recently published early-start antiplatelet treatment after neurosurgery in patients with spontaneous intracerebral hemorrhage (E-start) study indicates that for intracerebral hemorrhage patients with a high risk of ischemic events, early initiation of postoperative antiplatelet therapy can bring significant benefits without increasing the risk of bleeding. As the first high-level evidence-based evidence on perioperative management of intracerebral hemorrhage in China, the E-start study is instrumental in improving the treatment and management standards for intracerebral hemorrhage and enhancing patient outcomes.